PENERAPAN STRATEGI PEMBELAJARAN AKTIF KARTU ARISAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 3 PEKANBARU - Fitriani, Wahyu; Amran, Elva Yasmi; Erna, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: It has been applied the arisan card active learning strategy to improve students learning achievement on the subject of Hydrocarbons in class X of Senior High School Number 3 Pekanbaru. The research is an experimental research with pretest-posttest design. The samples of this research were the students of class X5 as the experimental class and the students of class X6 as the control class. They were randomly determined after given the tests of normality and homogeneity. Experimental class is a class which was given a treatment by applying active learning strategy of arisan card in learning process. The data were analyzed by using t-test. Based on the result of data analysis, it obtained tcount> ttable, which is 2,85 >1.67. It means that the application of active learning strategy of arisan card can improve student learning achievement on the subject of Hydrocarbons in class X of Senior High School Number 3 Pekanbaru. The improvement category of student achievement at experiment class was high category with normalized N-gain which is 0,81.Key Words: Active Learning Strategy, Arisan Card, Learning Achievement, Hydrocarbons